Cross-layer reliability of computing systems - Di Natale, Giorgio; Gizopoulos, Dimitris; Di Carlo, Stefano; Bosio, Alberto; Canal, Ramon (Materials, circuits and devices series ;, 2020)
This book presents state-of-the-art solutions for increasing the resilience of computing systems, both at single levels of abstraction and multi-layers. It is a valuable resource for researchers, postgraduate students and professional computer architects focusing on the dependability of computing systems